Determination of heavy metals in vegetables at Cameron Highlands / Noor Aniza Hussain - Hussain, Noor Aniza (Faculty of Applied Sciences, 2010)
Cameron Highlands is a highland region located about 121 km east of Ipoh and about 214 km north of Kuala Lumpur, in Pahang, Malaysia. This study is carried out in Cameron Highlands because it is the main source where the vegetables are produced and fulfill people need and also the biggest vegetables plantation in Malaysia. Five samples were collected based on different classification of vegetables and the samples were analyzed for their heavy metals content such as zinc, copper, lead and arsenic using Energy Dispersive X-Ray Fluorescence. The results show that zinc in green bean and water crest are above the maximum permitted level by Food Act 1983 and Food Regulation 1985 that is 60.81 mg/kg and 57.84 mg/kg respectively. Meanwhile, copper, lead and arsenic below the maximum permitted level. The value for the maximum permitted level for copper, lead and arsenic are 40.00 mg/kg, 2.00 mg/kg and 1.00 mg/kg respectively. In addition, heavy metal that contained in the vegetables mostly related to the heavy metals that are available in the soil.